Development of newer composite cement through mechano-chemical activation of steel slag. (25th January 2021) - Singh, S.K.; Jyoti,; Vashistha, Prabhat
Graphical abstract: Highlights: Physico-chemical characterization of LD slag shows presence of cementious phases in non-reactive crystalline form. Chappelle test and slag activity index test confirms its low reactivity. Mechano-chemical activation of slag significantly enhances the slag activity index. Sodium silicate and sodium sulphates increases compressive strength by 12.6% and 2.6% respectively as compared to control specimens. 30% of OPC can be gainfully replaced with sodium silicate or sodium sulphate activated LD slag for fabrication of cementitious binder. Abstract: The aim of present paper is to develop a composite cementitious binder by improving reactivity of Linz Donawitz (LD) slag through mechano-chemical activation. The pozzolanic reactivity of LD slag has been significantly improved as corroborated through modified Chapelle test and slag activity index. The mechanical grinding is carried out with ball milling of LD slag for 20 min followed by chemical activation with four different types of chemical activators namely sodium silicate, sodium sulphate, sodium hydroxide and sodium carbonate. The physico-chemical and strength properties were studied to quantify the efficacy of different alkali activators with 70% of ordinary Portland cement and 30% of ball milled LD slag blend. The sodium silicate and sodium sulphate alkali activators were found effective to enhance the reactivity, which led to increased compressive strength of developed cementitious binder paste cubes as compared to control paste cubes. XRD and Rietveld method results also exhibited the development of more calcium silicate hydrates (CSH) in activated binders, which corroborates increased compressive strength. The normalized heat flow and normalized heat were also found better for both these hydrated blend pastes in comparison to the other blends. The SEM analysis observed more hydration products morphology in blend pastes activated with sodium silicate and sodium sulphate. Based on outcome of different analytical techniques, it was observed that ball milling for 20 min and chemical activation with sodium silicate or sodium sulphate can be applied to enhance the reactivity of LD slag to develop a sustainable composite cement.